Education matters: longitudinal pathways to mid‐life heavy drinking in a national cohort of black Americans. - Mulia, Nina; Witbrodt, Jane; Karriker‐Jaffe, Katherine J.; Li, Libo; Lui, Camillia K.; Zapolski, Tamika (Addiction, 2022)
Aims: To estimate longitudinal pathways from childhood socio‐economic position (SEP) to educational attainment and mid‐life heavy drinking in black Americans in order to identify potential points of early intervention to reduce risk for alcohol‐related problems in adulthood. Design, Setting and Participants: Data are from 1299 black Americans in the US National Longitudinal Survey of Youth, followed from 1979 (aged 15–19 years) to 2012. Given gender differences in factors related to education and alcohol outcomes, gender‐stratified path models were analyzed. Measurements: Youth socio‐economic indicators included parental education (approximating childhood SEP) and adolescent poverty duration. Education‐related measures included high‐poverty school, perceived school safety, academic problems, suspension from school, educational expectations and educational attainment. Adulthood measures included repeated unemployment, poverty duration and mean frequency of heavy drinking (six or more drinks/day) in young adulthood and mid‐life. Covariates included age, dual‐parent household, marital status, early drinking onset and family history of alcohol problems. Findings For both genders, two main pathways originating from low childhood SEP flowed to educational attainment through (1) educational expectations and (2) suspension and from educational attainment to mid‐life heavy drinking [total indirect effect = 0.131, 95% confidence interval (CI) = 0.072–0.197 for women and 0.080, 95% CI = 0.035–0.139 for men]. For both genders, adolescent poverty (standardized βs ≥ 0.139), academic problems (βs ≥ 0.221) and school suspension (βs ≥ 0.166) were significantly (Ps < 0.05) related to lower educational expectations. In adulthood, educational attainment was indirectly protective against mid‐life heavy drinking through its significant effects (Ps < 0.05) on young adult heavy drinking for both genders (βs ≤ −0.204) and economic hardships for women (βs ≤ −0.372). Conclusions: Low childhood socio‐economic position among black Americans appears to be associated with subsequent, adverse socio‐economic and school experiences that lead to lower educational attainment and, ultimately, greater heavy drinking at mid‐life. Interventions that mitigate these earlier, adverse experiences might have indirect effects on mid‐life heavy drinking.